(untitled) (Politeja, 2022)
African Lisbon. Difficult Heritage, Postcolonial Relations, and Crosscultural Challenges The aim of this article is to synthetically capture African cultural influences from former colonies and various manifestations of the „African presence” in today’s Lisbon. This „African presence”, in a broad sense, includes a number of phenomena such as the living conditions and customs of the African diaspora in Lisbon, African elements in the cultural and tourist offer of the city, the activities of afrodescendentes (people of African origin) in the area of postcolonial relations, African traces in the topography of the city, and others. African cultural heritage is presented as dissonant, ambivalent, subject to various interpretations, also through the practices of post-memory. To illustrate these issues, I refer to a few examples of artistic projects and initiatives dealing with the topic of postcolonial relations in the Portuguese context.